Keperluan kursus dalam perkhidmatan untuk pembantu tadbir sekolah menengah di Bahagian Kuching/Samarahan - Kanyan Siam, Thomas (1998)
New development in civil service and financial weaknesses highlighted, generate a need for retraining. This study was designed to determine if there is a need for in-service course for Administrative Assistant to prepare for this change